Fluoroquinolone Resistance in Penicillin-resistant Streptococcus pneumoniae Clones, Spain - Adela G. de la Campa; Luz Balsalobre; Carmen Ardanuy; Asunción Fenoll; Emilio Pérez-Trallero; Josefina Liñares (Emerging Infectious Diseases, 2004)
Among 2,882 Streptococcus pneumoniae sent to the Spanish Reference Laboratory during 2002, 75 (2.6%) were ciprofloxacin-resistant. Resistance was associated with older patients (3.9% in adults and 7.2% in patients >65 years of age), with isolation from noninvasive sites (4.3% vs. 1.0%), and with penicillin and macrolide resistance. Among 14 low-level resistant (MIC 4–8 μg/mL) strains, 1 had a fluoroquinolone efflux phenotype, and 13 showed single ParC changes. The 61 high-level ciprofloxacin-resistant (MIC ≥16 μg/mL) strains showed either two or three changes at ParC, ParE, and GyrA. Resistance was acquired either by point mutation (70 strains) or by recombination with viridans streptococci (4 strains) at the topoisomerase II genes. Although 36 pulsed-field gel electrophoresis patterns were observed, 5 international multiresistant clones (Spain23F-1, Spain6B-2, Spain9V-3, Spain14-5 and Sweden15A-25) accounted for 35 (46.7%) of the ciprofloxacin-resistant strains. Continuous surveillance is needed to prevent the dissemination of these clones.